Modelagem da vazão e transporte de sedimentos suspensos na bacia hidrográfica do rio São Lourenço/MT - Balderrama, Vanesa Ponce (2019)
Many mathematical models of flow and sediment transport prediction have great potential to be used in the planning of water resources, because through these it is possible to estimate impacts caused by agricultural activities. Based on this assumption, the SWAT (Soil and Water Assessment Tool) model was used in a predominantly rural basin (22,199 km2 ) in the southeast of the State of Mato Grosso-MT, to evaluate its applicability to simulate flow and the transport of suspended sediments. For calibration and validation, measurements of three fluviometric and sedimentological stations (São Pedro da Cipa, São Lourenço and Rondonópolis) were available. The flow simulations were evaluated by means of visual analysis of the hydrographs and flow duration curves, and quantitatively from the determination coefficient (R2 ), the Nash-Sutcliffe index (NSE), the Kling-Gupta efficiency index (KGE ') and Bias Percentage (PBIAS). Due to the limited performance of the monthly simulation, with a NSE of -1,13 to -0,16, a sensitivity and calibration analysis was performed for the period (2004-2012) and validation (2013- 2016), making the results satisfactory for the Calibration of between 0.46 and 0.64 and for the validation of between 0,65 and 0,67. The monthly simulations of suspended sediments adequately represented the annual transport cycle, but with sub / superestimates between 29,4 and 395,4 % for the initial simulation, already in the simulation after the calibration I had a sub / overestimate of 5,5 and 152.5. In addition, a sediment yield map was generated for the São Lourenço River Basin where the areas with the highest sediment production (Campo Verde, Jaciara, Dom Aquino, Poxoréo and Pedra Preta) them were identified land use, soil types and declivity for these areas of higher production.